Simplified Social Mediated Crisis Communication Model during Crisis in Indonesia: A Case Study on How Customers of Indonesia Commuter Line Train Company Seek Information on a Train Delay Due to the Double Track Trial on April 12, 2019 - Adi, Wasono (KnE Social Sciences, 2020)
This study explores how audiences seek information from internet and social media platforms, and considers what factors affect social media use during a crisis. The paper is based on research conducted via a survey involving 162 active followers selected from the 875,200 followers of the Indonesia Train Company: PT Kereta Api Commuter Line official Twitter account (Info Commuter Line @CommuterLine). The study proposes the Simplified Social Mediated Crisis Communication Model (SSMCC) as a variation on the original Social-Mediated Crisis Communication (SMCC) Model by Jin & Liu (2010). This variation is based on the argument that during a crisis, audiences located nearby typically rely on social media (usually accessed via a mobile phone) rather than a traditional media outlet when seeking information. This study concludes that some of the themes related to the use of social media to search for information during a crisis, and word of mouth (WOM) communication, are present in the Social-Mediated Crisis Communication (SMCC) communication model. This study also discusses the differences between the original SMCC model and the Simplified Social-Mediated Crisis Communication model proposed by the researcher. There was no evidence of an inactive social media user’s influence on information retrieval during a crisis; in addition, there is no role of traditional media as a source of information retrieval during a crisis. This research contributes to developing scientific knowledge and practices in Indonesia. Keywords: crisis communication, social media, information search, simplified social mediated crisis communication model, social media followers